Evaluasi Efektivitas Program Literasi Digital terhadap Kesadaran Privasi Data dan Etika Bermedia Sosial - Winarsih, Tutik; Resmawa, Ira Ningrum; Triono, Bambang (Transpublika Publisher, 2025)
Rapid digital development brings serious challenges related to personal data protection and social media ethics, especially among students who will enter the technology-based workforce. Responding to this need, the team from the YAPAN College of Economics carried out a community service program entitled